1995
DOI: 10.1164/ajrccm.152.6.8520757
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of leukocyte counts in sputum, bronchial biopsies, and bronchoalveolar lavage.

Abstract: To determine the relationship between inflammatory cells in sputum, bronchoalveolar lavage (BAL), and bronchial mucosa, we counted the number of leukocytes in sputum, BAL, and bronchial biopsies obtained from subjects with asthma and with chronic bronchitis in stable condition or during exacerbations. Sputum was induced by inhalation of hypertonic saline in the asthma group. Spontaneous sputum was collected in the chronic bronchitis groups. Differential counts of leukocytes were performed on cytospin preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
160
2
7

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(184 citation statements)
references
References 10 publications
15
160
2
7
Order By: Relevance
“…This observation may indicate that sputum is not the right representative compartment to assess an influence of inflammation on AHR in COPD. Results of two previous studies comparing bronchoalveolar lavage, sputum and airway wall biopsies have already suggested that sputum inflammatory assessments are not representative for inflammation throughout the lung [22,34]. Yet another interpretation of the current authors9 findings is that the increase in neutrophils, already seen after 6 months smoking cessation, is just a reflection of a decrease in neutrophils in the airway wall and, thus, sputum could be regarded as a "rubbish bin" in COPD.…”
Section: Discussionmentioning
confidence: 53%
“…This observation may indicate that sputum is not the right representative compartment to assess an influence of inflammation on AHR in COPD. Results of two previous studies comparing bronchoalveolar lavage, sputum and airway wall biopsies have already suggested that sputum inflammatory assessments are not representative for inflammation throughout the lung [22,34]. Yet another interpretation of the current authors9 findings is that the increase in neutrophils, already seen after 6 months smoking cessation, is just a reflection of a decrease in neutrophils in the airway wall and, thus, sputum could be regarded as a "rubbish bin" in COPD.…”
Section: Discussionmentioning
confidence: 53%
“…The first is that sputum eosinophils is a sensitive indicator of airway inflammation which develops before clinical exacerbations of asthma [4]. The second is that from the two studies so far comparing sputum with biopsies, when sputum cell counts are normal, usually no eosinophils were found in the biopsies [16,17]. The evidence therefore suggests that in the assessment of the presence and type of airway inflammation, objective measurement by sputum cell counts is more accurate than indirect clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Although sputum examination has not been established as the "gold standard" for sampling airway secretions, it provides cell counts qualitatively similar to those obtained by analysis of bronchial wash [14,15], lavage [14±18] and biopsy [16,17]. The authors considered that if the clinical assessment of the presence and type of airway inflammation compared well with the sputum cell counts, then this additional test may not be useful in practice.…”
mentioning
confidence: 99%
“…23,24 However, when the eosinophil count was expressed as normal and abnormal values on the basis of the results from healthy controls, significant agreement could be found between sputum eosinophilia and presence of eosinophilic inflammation in bronchial mucosa. 23 Because, in this study, sputum eosinophil count was used to monitor the presence of eosinophilic inflammation in the bronchial mucosa of atopic asthmatics, we expressed the results of sputum eosinophil count in asthmatic patients as normal and abnormal values on the basis of data from healthy controls for statistical analysis. The validity of the cut-off value of sputum eosinophil count (Ն5%) used in this study also has been verified by another group using 41 asthmatic patients and 27 nonasthmatic subjects.…”
Section: Discussionmentioning
confidence: 94%